Understanding leakage from a fault-sealed CO2 reservoir in east-central Utah: a natural analogue applicable to CO2 storage - Dockrill, Ben (Trinity College (Dublin, Ireland). Department of Geology, 2006)
This thesis investigates a natural CO2 reservoir to define the factors that can cause leakage and determine the rates and consequences of CO2 leakage on the surrounding environment. Situated at the northern end of the Paradox Basin in east- central Utah, faulting of the north-plunging Green River Anticline has created structural highs in the footwalls of the west-north-west trending Little Grand Wash Fault and northern fault of the Salt Wash Graben. Focussed surface leakage of CO2 is prevalent in the immediate footwalls of both faults with the presence of C02-charged geysers and springs and travertine deposits. The C02-rich waters erupting from the geysers and springs are a product of CO2 produced from clay-carbonate reactions in Triassic and sub-Permian source beds rising and mixing with a series of overlying stacked aquifers (Heath, 2004). Geochemical investigations of active and ancient travertines along both faults indicate that this hydrologic system has been prevalent for at least the last 78,000 years.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin